Em memória das mãos: o desencantamento da técnica na arquitetura e no urbanismo - Lopes, João Marcos de Almeida (2006)
The ideal ways of composition betwen matter and form establish opositions that contributes for a dualist conception of the world. The production of the Building and the City is, historicaly, deeply marked by this conception, organizing the technical activity in the practice of the architect and urbanist trade in diferent fields and, anytime, opposites: form & function, form & contents, theory & practice or even mesmo theory & technic. Through a fenomenology of the technics exercises and of the technics object existence way, I try to grasp some essenciality in the technics activity by itself. After this, reintroductioned the technics action and the technics objets in the world of life, trying to grasp how is the transformation of technic into technology, alleged how undelighted agency of the arguments in a technical racionality. Starting form its development in the history, I resume some technological conceptions wich is controling the architectural debate in the presents times and to them I stand against one conception of technical action non hilemorphic in the practice of the trade.